Developing Comic Media for Reading Comprehension Ability of Historical Texts in Elementary School Students - Liza Murniviyanti; Arita Marini (Universitas Pendidikan Indonesia Kampus Serang, 2021)
Students' reading comprehension skills were still low since the existing media only relied on teaching materials in schools such as books and worksheets. Thus, it has not been able to make effective learning. This research and development aimed to produce comics learning media for historical text narrative to read and understand Indonesian language learning for fifth-graders of elementary school. Comics are information presented through conversation by pictures, arranged conceptually and interestingly to make it easier to understand the information. This comic was developed to be used in learning and improving reading comprehension skills. This research and development used ADDIE development procedures including (1) Analyze, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. The subjects of the one-to-one trial were three students, the small group trial subjects were six students, and the implementation subjects were 15 students. The results showed that the comic media was feasible with an average percentage of 81.7% from the experts in the appropriate category. The average student responses indicated that students were happy to read comics as a learning medium in the learning process with a percentage of 95%. Based on the pretest and the posttest results, the developed comic media had increased the learning outcomes of fifth-graders at the Elementary School of 22 Palembang by 0.42 with a moderate improvement category according to the N-Gain scale. Thus, it can conclude that the development of historical text narrative comic media was appropriate for the reading comprehension ability of fifth-graders of the Elementary School of 22 Palembang.